Restoration of the Outer Treasury and Exhibition of the Section of Arms and Armours in Topkapi Palace Museum - Diker, Hasan Fırat (Elsevier Science Bv, 2012)
This article aims at telling the story of restoration and exhibition of the Section of Arms and Armours (the Outer Treasury) in Topkapi Palace Museum. During this process, not only was the structure experiencing restoration and consolidation, but also was the first archeological excavation being realized in a closed space in the Topkapi Palace complex, with the discovery of Byzantine reminiscences underground becoming a significant part of the new exhibiton.After being restored between 2008 and 2010, the Outer Treasury was transformed into a new exhibition project, aiming at the integration of contemporary strategies of exhibition design and technology. Its purpose was not simply to highlight the glory of the Ottoman history, but to engage visitors in a complete sensory experience by making full use of the esthetics of the work of art on display of the Ottoman legacy. Topkapi Palace's architecture, archeology and selected collection of arms and armours are being exhibited by means of contemporary media instruments, such as film, music, graphics and costume arts. (C) 2012. Higher Education Press Limited Company. Production and hosting by Elsevier B.V.
Keywords: Topkapipalace; Ottoman; Byzantine; Arms Andarmours; Restoration; Exhibition